Macrozoobentos Diversity in Freshwater Waters of Rainforest Lodges Kedah, Blangjerago District, Gayo Lues Regency - Haryati Haryati; Iswadi Iswadi; mimie saputri; M Ali Sarong; Devi Syafrianti (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Keywords: Macrozoobentos, Diversity, River Rainforest Lodges Kedah. Rainforest Lodges are a tourist attaraction that is also used as a place for research activities. Various human activities such as disposal of industrial waste and household waste cause a decrease in river water quality, resulting in the river is no longer able to recover resulting in diversity of aquatic biota, one of which is macrozoobenthos activity. The study was conducted in September to October 2019. The purpose of this study was to determine the level of macrozoobenthos diversity, and to determine the physical and chemical conditions of the waters. The method used is a survey method, with a purposive sampling, technique based on the presence of freshwater macrozoobentos. Data analysis uses the Shannon-Wiener diversity index formula. The result of the study were 15 macrozoobentos species from 15 families. Diversity index at each station I with H'= 1,63, at station II with H'= 2,08, and at station III with H'= 1,70.  The conclusion in this study is the level of diversity of macrozoobenthos species the waters of the Rainforest Lodges Kedah, Blangjerango District, Gayo Lues Regency is classified as moderate (range 1,63-2,08). And the result of measurements obtained physical chemistry of aquatic factors obtained ranged from 27º C-30º C, the pH water obtained ranges from 7,5-8,9, depth ranges between 1,2-1,4 m. Depth ranges between as for salinity 0‰-0,01‰.Kata kunci : keanekaragaman, makrozoobentos, sungai Rainforest Lodges Kedah Rainforest Lodges Kedah adalah satu tempat wisata yang juga dijadikan tempat untuk kegiatan penelitian. Banyaknya aktivitas manusia seperti pembuangan limbah industri, limbah rumah tangga mengakibatkan menurunnya kualitas air sungai, menjadikankan sungai tidak mampu lagi melakukan pemulihan, berakibat pada keanekaragaman biota perairan salah satunya aktivitas makrozoobentos. Penelitian dilaksanakan pada bulan September sampai Oktober 2019. Tujuan penelitian ini untuk (1) mengetahui tingkat keanekaragaman makrozoobentos, dan untuk (2) mengetahui kondisi fisika dan kimia perairan. Adapun Metode yang digunakan yaitu metode survey, dengan teknik purposive sampling, berdasarkan kehadiran makrozoobentos air tawar. Analisa data menggunakan rumus indeks keanekaragaman Shannon-Wiener. Hasil penelitian terdapat 15 spesies makrozoobentos dari 15 famili. Indeks keanekaragaman di setiap stasiun, stasiun I dengan H'= 1,63, pada stasiun II dengan H'= 2,08, dan pada stasiun III dengan H'= 1,70.  Adapun kesimpulan penelitian ini adalah tingkat keanekaragaman spesies makrozoobentos di perairan sungai Rainforest Lodges Kedah Kecamatan Blangjerango Kabupaten Gayo Lues tergolong sedang (kisaran 1,63-2,08) dan hasil pengukuran faktor fisika-kimia yang diperoleh berkisar antara 27º C-30º C, pH air diperoleh berkisar antara 7,5-8,9, kedalaman berkisar antara 1,2-1,4 m. Sedangkan untuk salinitas adalah 0‰-0,01‰.